GROWING INTEREST IN LITERATURE AND DEVELOPMENT OF SCIENCE TECHNOLOGY IN SMP AL FALAH KRATON - Siti Nur Hidayati; Dida Rahmadanik (Literasi Nusantara, 2022)
The teaching campus is one of the programs from Merdeka Learning Merdeka Campus (MBKM) to assist the learning process in elementary and junior high schools in various parts of the country, especially in the 3T area. This program is based on the fact that learning has not been implemented effectively during the Covid-19 pandemic which has caused learning loss for students. Considering the 3T area, many people are in the lower middle economic class, not everyone has a smart smartphone . One of them is at the AL Falah Kraton Pasuruan Middle School who experienced this problem and required him to organize a learning process during the Covid-19 pandemic with the permission of the Pasuruan Regency Education Office along with the requirements of strict health protocols and have carried out dose one and two vaccinations. Based on these problems, the presence of campus students teaching at SMP AL Falah Kraton Pasuruan can help contribute to conducting effective learning during the Covid-19 pandemic. The programs held include focusing on developing a literacy and numeracy culture, adapting technology and school administration. The research method used is a qualitative approach and data collection techniques are carried out by observation and documentation techniques.